BAURAN PEMASARAN JASA TERHADAP LOYALITAS NASABAH (STUDI KASUS DI PT. BANK BNI SYARIAH CABANG PALEMBANG) - AKBAR, DINNUL ALFIAN (Islamic Economics Program, Faculty of Islamic Economics and Business, 2016)
The aim of this research is to know the relationship service marketing mix has influence to customer loyalty saving in PT. Bank BNI Syariah Palembang branch and to know which service marketing mix variable that dominant influence to customer loyalty saving in PT. Bank BNI Syariah Palembang branch. The population in this research is the customers who have saving account in PT. Bank BNI Syariah. Based on the population that are 31.794 customers with customers characteristic who have saving account in PT. Bank BNI Syariah more than one year. Sampling technique using incidental sampling that are 100 samples with multiple linear regression analysis. Finally the result of this research showed that service marketing mix (product (X1), price (X2), place (X3), promotion (X4), people (X5), physical evidence (X6), and process (X7)). ) Simultaneously have positive significant influence to customer loyalty saving in PT. Bank BNI Syariah Palembang branch. Product variable is the dominant variable which influence customer loyalty saving in PT. Bank BNI Syariah Palembang branch.Key word: service marketing mix, product, price, place, promotion, people, physical evidence, process, and customer loyalty.